The different symptoms determining management of hand foot and mouth disease and primary varicella zoster infection - Maharani Laillyza Apriasari (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Hand, foot and mouth disease (HFMD) is a medical condition endemic among children in South-East Asia, including Indonesia and, more specifically, Banjarmasin – the capital of South Sulawesi. The disease is mediated by Enterovirus 71 and Coxsackievirus 16 which attack the oral cavity, hands, feet, buttocks and genital areas. One differential diagnosis of this disease is Primary Varicella Zoster infection. Both diseases have similar clinical symptoms but different etiologies which can precipitate errors in the administration of therapy Purpose: To elucidate the distinction between HFMD and Primary varicella zoster infection. Case: An 8 year-old male sought treatment complaining of ulcers on the upper maxillary gingiva followed by the appearance of itchy and painful lesions affecting the nose, upper lip, hands and feet. The patient’s mother reported his history of 39oC fever followed by the development of red spots and ulcers on the face, hands and feet which caused itching. Clinically, it is similar to Primary varicella zoster infection which can affect any part of the body. The patient only used an immunomodulator once a day and was actively seeking available healthcare. Case management: Extraoral examination confirmed the presence of multiple erythematous vesicles and ulcers, 2 mm in diameter, which caused a sensation of itching around the nose and upper lip region. Multiple painful and itchy red macules and vesicles, 3-6 mm in diameter, appeared not only on the patient’s palms, back of the hands and feet. Intraoral examination of the right maxillary gingiva revealed multiple painful ulcers, 1-2 mm in diameter and yellowish in appearance, surrounded by erythema. The results of history-taking implied that no lesions appeared on other parts of the body. Conclusion: While these conditions share similar clinical manifestations, their contrasting etiologies require different treatments. The ultimate diagnosis can be determined clinically by the dentist, thereby preventing errors in the administration of therapy.